2020
DOI: 10.1186/s13071-020-04470-y
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of dengue virus in individual Aedes aegypti mosquitoes collected concurrently with suspected human cases in Tarlac City, Philippines

Abstract: Background Vector control measures are critical for the prevention and reduction of dengue virus (DENV) transmission. Effective vector control is reliant not only on knowledge of mosquito abundance, but also on the timely and accurate detection of mosquito-borne infection. Mosquito-based virus surveillance programs typically rely on pool-based mosquito testing, although whether individual-based mosquito testing is a feasible alternative to this has not been widely studied. Applying an individua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…Since most of the cases were children and adults ( S4 Table ) who have spent day time outside their residence (e.g., school, worksite/office), it is possible that they were exposed there to infectious mosquitoes. This finding is consistent with previous studies conducted in Brazil and Philippines that found differences in DENV serotypes between patients and mosquitoes in the same home [ 32 , 35 ]. Previous reports suggest that DENV infection often occurs elsewhere, other than the home, e.g.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Since most of the cases were children and adults ( S4 Table ) who have spent day time outside their residence (e.g., school, worksite/office), it is possible that they were exposed there to infectious mosquitoes. This finding is consistent with previous studies conducted in Brazil and Philippines that found differences in DENV serotypes between patients and mosquitoes in the same home [ 32 , 35 ]. Previous reports suggest that DENV infection often occurs elsewhere, other than the home, e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Previous reports suggest that DENV infection often occurs elsewhere, other than the home, e.g. workplace, school or college, temple or farm field [ 9 , 35 , 52 ]. Numerous factors may influence these results including: i) asymptomatic infections with different DENV serotypes in members of the same household, ii) transovarial transmission of DENV in the household involving serotypes to which the residents have recent prior immunity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adult mosquitoes were collected by installing commercially available mosquito UV light trap (MosquitoTrap, Jocanima Corporation, Las Piñas, Philippines) for 48 hours either inside or outside of each household. The UV light trap produces heat and CO 2 gas attracting mosquitoes to enter into the capture net via a strong current from the ventilator [27]. In each household, one mosquito trap was installed.…”
Section: Collection Sampling and Identificationmentioning
confidence: 99%
“…We set the mosquito trap for 48 hours inside or outside the surveyed households. The mosquito trap attracts the host-seeking and blood-fed mosquitoes to enter a capture net via the heat and CO 2 transmitted by a strong current from the ventilator (Balingit et al, 2020; Regilme et al, 2021). We also surveyed water containers in each household ( n = 428) and found 17 containers with Aedes larvae ( n = 509) outside the premises of 14 households.…”
Section: Methodsmentioning
confidence: 99%